Hyperbaric oxygen therapy for the treatment of a crush injury of the hand: a case report - Pedro Henry Neto; Zamara Brandão Ribeiro; Adriano Bastos Pinho; Carlos Henrique Rodrigues de Almeida; Carlos Alberto de Albuquerque Maranhão; Joaquim da Cunha Campos Goncalves (Journal of Trauma and Injury)
We describe a case of hyperbaric oxygen therapy (HBOt) as an adjunct to treatment of a crush injury to the hand. A 34-year-old male paramedic was involved in a motor vehicle accident and admitted for diagnosis and surgical treatment. He sustained a crush injury to his right hand and presented with significant muscle damage, including multiple fractures and dislocations, an avulsion injury of the flexor tendons, and amputation of the distal phalanx of the little finger. He underwent reconstructive surgery and received HBOt over the following days. In the following 2 months, he lost the distal and middle phalanges of the little finger and recovered hand function. Posttraumatic compartment syndrome responds well to HBOt, which reduces edema and contributes to angiogenesis, as well as promoting the cascade of healing events. High-energy trauma causes massive cell destruction, and the blood supply is usually not sufficient to meet the oxygen demands of viable tissues. Hyperbaric oxygenation by diffusion through interstitial and cellular fluids increases tissue oxygenation to levels sufficient for the host’s responses to injury to work and helps control the delayed inflammatory reaction. HBOt used as an adjunct to surgical treatment resulted in early healing and rehabilitation, accelerating functional recovery. The results suggest that adjunctive HBOt can be beneficial for the treatment of crush injuries of the hand, resulting in better functional outcomes and helping to avoid unnecessary amputations.